2015
DOI: 10.1021/cn500363g
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Angiotensin-Converting Enzymes and Their Modulators in Neurodegenerative Disorders: Current and Future Perspectives

Abstract: Angiotensin converting enzyme (ACE) is a dipeptidyl peptidase transmembrane bound enzyme. Generally, ACE inhibitors are used for the cardiovascular disorders. ACE inhibitors are primary agents for the management of hypertension, so these cannot be avoided for further use. The present Review focuses on the implications of angiotensin converting enzyme inhibitors in neurodegenerative disorders such as dementia, Alzheimer's disease, Parkinson's disease, Huntington's disease, amyotrophic lateral sclerosis, stroke,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 179 publications
0
32
0
1
Order By: Relevance
“…One-way ANOVA followed by Tukey's post-tests were performed, **p < 0.01, ***p < 0.001, n = 4 for each group angiotensin receptors (AT 1 -R and AT 2 -R) and regulates not only blood pressure, cerebral blood flow, and homeostasisassociated behaviors [35][36][37], but also motor activity, learning, and memory [38,39]. The ACE inhibitor, perindopril, is able to penetrate the blood-brain barrier and modulate striatal DA synthesis and release [11], and prevents the development of Alzheimer's and Parkinson's disease [40,41]. Our results unequivocally showed that perindopril decreased the expression of striatal Ang II and attenuated METH-induced hyperlocomotor, suggesting the involvement of ACE and Ang II in the formation of hyperlocomotor induced by METH.…”
Section: Discussionmentioning
confidence: 99%
“…One-way ANOVA followed by Tukey's post-tests were performed, **p < 0.01, ***p < 0.001, n = 4 for each group angiotensin receptors (AT 1 -R and AT 2 -R) and regulates not only blood pressure, cerebral blood flow, and homeostasisassociated behaviors [35][36][37], but also motor activity, learning, and memory [38,39]. The ACE inhibitor, perindopril, is able to penetrate the blood-brain barrier and modulate striatal DA synthesis and release [11], and prevents the development of Alzheimer's and Parkinson's disease [40,41]. Our results unequivocally showed that perindopril decreased the expression of striatal Ang II and attenuated METH-induced hyperlocomotor, suggesting the involvement of ACE and Ang II in the formation of hyperlocomotor induced by METH.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that angiotensin receptors are expressed in nociceptive processing brain and spinal cord areas and drugs that block some of these receptors (AT1Rs) are strongly neuroprotective. The AT2 receptor is upregulated in injured nerves and their DRGs . Angiotensinogen is processed into eight smaller proteins and peptides with known roles in the renin‐angiotensin system (RAS), including angiotensin‐1, angiotensin‐2, angiotensin‐3, and angiotensin 1‐7.…”
Section: Discussionmentioning
confidence: 99%
“…It was originally reported that the ACE activity levels in D/D carriers were approximately twice those found in I/I genotype individuals [ 34 ]. Therefore, this indel polymorphism was used as a marker for studying associations with pathophysiological conditions, including neurodegenerative diseases, such as PD [ 10 ]. Moreover, the ACE indel polymorphism in the Australian Caucasian population was not associated with PD in the first association study [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin converting enzyme (ACE), a membrane-bound zinc metallopeptidase, regulates blood pressure and blood volume by converting angiotensin I to angiotensin II and by degrading bradykinin. Previous studies have suggested that it may be involved in the pathogenesis of neurodegenerative disorders such as PD, AD, Huntington’s disease, and autism [ 10 , 11 ]. Furthermore, the primary loss of substance P due to ACE hydrolysis has been shown to be a contributing factor in the pathogenesis of PD [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%